THE RELATIONSHIPS BETWEEN SELECTED DEMOGRAPHIC FACTORS AND ACCEPTABILITY OF CONSUMER INSURANCE FRAUD - Brokesova, Zuzana; Pastorakova, Erika (European Scientific Journal, ESJ, 2014)
Consumer insurance fraud represents considerable problem in insurance industry. The association of European insurers – the Insurance Europe – estimates that detected and undetected consumer fraud represents up to 10% of all claims expenditure in Europe (Insurance Europe, 2012). In theoretical and empirical research, incentives for committing this type of fraud are explained variously. However, the role of demographic factors is marginalized. In this paper, we analyze the relationships between selected demographic factors and the level of acceptability of insurance fraud commitment among Slovak respondents. Even thought that acceptability of consumer insurance fraud does not represent the real action, these two variables are strongly linked. Based on our results, we could conclude that the level of insurance fraud acceptability among the respondents varies based on their age, gender, level of education and religion. In line with previous research, we find that women, highly educated individuals and elderly individuals understand different types of fraudulent behaviour as less acceptable. In addition, our study analyzes the role of religion and income level. Whereas in the case of religiosity, we confirm our assumption that respondents who declared themselves as believers in whose lives religion plays important role understand consumer insurance fraud as more unacceptable than nonbelievers, the role of personal income stays unclear.